Evolusi Leksikografi Arab: Analisis Model Penyusunan Kamus dari Tradisi Klasik hingga Korpus Digital - Martiana, Wilsa; Siregar, Husnatul Hamidiyyah (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
This study examines the evolution of Arabic dictionary compilation models from classical to modern times within the framework of lexicology. The background of this study lies in the importance of dictionaries as key instruments in understanding vocabulary, word structure, and the dynamics of meaning in Arabic, while also responding to the needs of users in the contemporary era. The main questions of this study are: (1) how has the model of Arabic dictionary compilation developed from the classical to the modern era? and (2) what are the implications for the analysis of meaning and word structure in Arabic lexicology? This study aims to reveal methodological changes in Arabic lexicography and its contribution to the study of morphology and semantics. The research method uses a qualitative approach with literature study and descriptive-analytical analysis of primary and secondary sources, including classical, modern, and digital dictionaries. Data validity is strengthened through source triangulation. The results show that classical dictionaries emphasize root systems, makhraj, and authoritative quotations, especially in explaining morphological structure and static meaning. In the modern era, the compilation model has shifted to a more practical alphabetical system, complemented by contemporary linguistic analysis and the fulfillment of Arabic language learners' needs. Meanwhile, digital and corpus-based dictionaries present significant innovations through automatic analysis, dynamic semantic mapping, and technology-based lexical processing. This transformation not only enriches Arabic linguistic resources but also opens up opportunities for the integration of lexicology with computational linguistics. Thus, the evolution of dictionary compilation models shows a shift from traditional approaches to models that are more interactive, adaptive, and responsive to language developments.